2009
DOI: 10.1007/s00246-009-9603-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Epinephrine Test in the Diagnosis and Management of Children Suspected of Having Congenital Long QT Syndrome

Abstract: The epinephrine test has been shown to be a powerful tool to predict the genotype of congenital long QT syndrome (LQTS). The aim of this study was to evaluate its role in the diagnosis and management of LQTS in children. The test (using the Shimizu protocol) was conducted in patients with some evidence of LQTS but in whom clinical and management decisions were challenging (n = 41, age 9.6 ± 3.9 years, 19 female). LQT1, LQT2, and negative responses to epinephrine were obtained in 16, 5, and 20 subjects, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“… 25 Indeed, stress testing of patients via sympathetic stimulation by the β-adrenoreceptor agonist, isoprenaline, has been employed to exacerbate and diagnose LQTS. 26 To determine whether arrhythmic events could be recapitulated in vitro , patient-specific and control cardiomyocytes were treated with isoprenaline ( Figure 5 ). In beating clusters, isoprenaline caused a similar reduction in FPD of control (20.4 ± 11.8%; data pooled for MAT–hiPSC, HF–hiPSC, and HUES7) and LQT2–hiPSC (24.1 ± 12.7%; P > 0.05; Figure 5 A ).…”
Section: Resultsmentioning
confidence: 99%
“… 25 Indeed, stress testing of patients via sympathetic stimulation by the β-adrenoreceptor agonist, isoprenaline, has been employed to exacerbate and diagnose LQTS. 26 To determine whether arrhythmic events could be recapitulated in vitro , patient-specific and control cardiomyocytes were treated with isoprenaline ( Figure 5 ). In beating clusters, isoprenaline caused a similar reduction in FPD of control (20.4 ± 11.8%; data pooled for MAT–hiPSC, HF–hiPSC, and HUES7) and LQT2–hiPSC (24.1 ± 12.7%; P > 0.05; Figure 5 A ).…”
Section: Resultsmentioning
confidence: 99%
“…In this patient, we prescribed metoprolol before obtaining the results of the genetic examination. This was because (a) beta-blocker is believed to be a first line medical treatment in most of the LQTS patients [18][19][20], and (b) results of the epinephrine infusion test and treadmill exercise test suggested either type-1 or type-2 LQTS [21][22][23]. Although magnitude of the QTc interval prolongation by the two tests were mild, type-3 LQTS seemed less likely because the QTc interval was not shortened by sympathetic stimulation.…”
Section: Discussionmentioning
confidence: 94%
“…21 In a systematic analysis, the epinephrine test, which is used to diagnose concealed iLQTS, no single episode of epinephrineinduced TdP or ventricular fibrillation occurred in more than 500 patients with iLQTS. 11 In contrast Clur et al 22 reported nonsustained ventricular tachycardia in patients with LQTS receiving epinephrine during the provocation test, despite the fact that the epinephrine bolus (0.1 mg/ kg) is much lower than the epinephrine dosage used for treating anaphylaxis. In a case report, the injection of epinephrine caused a marked prolongation of the QT interval, followed by polymorphic ventricular tachycardia, which could be terminated by direct cardioversion 23 ; therefore, LQTS was suspected.…”
Section: Epinephrine (Adrenaline)mentioning
confidence: 95%